Genome‐wide identification of urinary cell‐free microRNAs for non‐invasive detection of bladder cancer - Juracek, Jaroslav (J Cell Mol Med, 2018)
Urinary microRNAs (miRNAs) are emerging as clinically useful tool for early and non‐invasive detection of various types of cancer including bladder cancer (BCA). In this study, 205 patients with BCA and 99 healthy controls were prospectively enrolled. Expression profiles of urinary miRNAs were obtained using Affymetrix miRNA microarrays (2578 miRNAs) and candidate miRNAs further validated in independent cohorts using qRT‐PCR. Whole‐genome profiling identified 76 miRNAs with significantly different concentrations in urine of BCA compared to controls (P < 0.01). In the training and independent validation phase of the study, miR‐31‐5p, miR‐93‐5p and miR‐191‐5p were confirmed to have significantly higher levels in urine of patients with BCA in comparison with controls (P < 0.01). We further established 2‐miRNA‐based urinary DxScore (miR‐93‐5p, miR‐31‐5p) enabling sensitive BCA detection with AUC being 0.84 and 0.81 in the training and validation phase, respectively. Moreover, DxScore significantly differed in the various histopathological subgroups of BCA and decreased post‐operatively. In conclusion, we identified and independently validated cell‐free urinary miRNAs as promising biomarkers enabling non‐invasive detection of BCA.